Haemophilus influenzae type b and pneumococcal conjugate vaccination coverage in children aged 2-59 months in Malawi - Daphne Gadama; Tisungane Mvalo; Amy Sarah Ginsburg (Taylor & Francis Group, 2021)
High vaccination coverage with Haemophilus influenzae type b (Hib) and pneumococcal conjugate vaccines is critical to addressing childhood pneumonia's high mortality. The Innovative Treatments in Pneumonia project in Lilongwe, Malawi collected Hib and pneumococcal vaccination information from children's health passports and found the majority demonstrated inadequate and inconsistent documentation. We were unable to confidently assess the impact of Hib and pneumococcal vaccination on pneumonia treatment failure in our study population. Whether it be that enrolled children did not receive age-eligible vaccines or there was poor vaccination record-keeping, we do not know. A shift to an electronic data collection system may help ensure capture of essential vaccination data and provide more accurate records of both individual and population vaccination coverage in Malawi.